PRESSURE ULCER IN THE ELDERLY IN A UNIVERSITY HOSPITAL: PREDISPOSING CONDITIONS, RISK FACTORS INTRINSIC AND EXTRINSIC (Fiep Bulletin - online, 2013)
The pressure ulcers (PU) are areas of cell death, which develop when a soft tissue is compressed between a bone prominence and a hard surface for a long time. The predisposing conditions (PC), intrinsic factors (FI) and extrinsic (EF) influence on the occurrence of UP, because interfere with the normal physiology of the body. This paper aims to identify the predisposing conditions, risk factors intrinsic and extrinsic in the occurrence of PU in elderly patients hospitalized in a University Hospital of Natal / RN. Study descriptive and quantitative approach, with 30 patients in the clinical areas of medical, surgical clinic, neurology and ICU. After approval by the Commission on Ethics in Research of HUOL / UFRN (Opinion No. 135/07), was conducted to collect data from 13/12/2007 to 20/01/2008, using medical records and structured form. The data were analyzed with SPSS 15.0. Of the patients, 46.7% developed UP, and 50.0% elderly, 57.1% female. The main regions of UP were sacral (85.7%) and trochanteric (28.6%). The PC, IF and EF were more present in the elderly, and the main predisposing conditions: use of analgesics (64.3%) and hematological and psychogenic (57.1%); intrinsic factors: changes in texture (64.3%) , Temperature, and elasticity of skin turgor and physical mobility impaired partial (57.1%); extrinsic factors: pressure from the body, lifting the head = 30 degrees, conditions of bed linen and mobility inadequate (even decubitus> 2h) (64 , 3%); type of mattress inadequate (57.1%). The weaknesses of the elderly help to change their lifestyle, the compromises sensory perception, activity, mobility, nutrition and characteristics of the skin, requiring assistance more effective and focused on prevention of UP and its complications, responsible for an increase in morbidity and mortality and costs in hospitalization.
Keywords: pressure ulcer; aged; risk factors